A study on correlation between laterality of placenta on mid trimester ultrasonography and perinatal outcome - Ghosh, Avik; Ghosh, Mrinalkanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Fetus is dependent on placenta for supply of nutrients from mother. Objective of this study was to assess the relationship between laterality of placenta by mid-trimester ultrasonography and perinatal outcome. Methods: It was a prospective observational study conducted between June 2016 to June 2017 at Burdwan Medical College, West Bengal. Participants were uncomplicated pregnant women having 18-24 weeks gestation attending antenatal clinics and admitted in ward who underwent obstetric sonography including placental localization. Women were observed till delivery. Analysis was done for site of implantation of placenta and its correlation with perinatal outcome. Results: Total of 300 women considered for the study, 195/300 (65%) had central implantation of placenta and 105/300 (35%) had lateral type of placentation. There were 4 IUFDs (1.33%); 2 (1.03) with central placenta and 2 (1.9) with lateral placenta. Among 31 (10.33%) IUGR babies 13 (6.67%) were associated with central and 18 (17.14%) with lateral placenta. Among 27 LBW babies 16 (8.21%) were related to central placenta and 11 (10.48%) were related to lateral placenta. Among 57 SNCU admissions 26 (13.33%) were related to central placenta and 31 (29.52%) were related to lateral placenta. Average birth-weight is 2.6±0.31 kg and 2.51±0.26 kg, respectively for central and lateral placenta. Conclusions: Laterally located placenta is associated with relatively poor perinatal outcome compared to central placenta with increased rates of IUGR, IUFD and LBW babies.